Mellem Skylla og Charybdis – træk af legalitetsprincippets historie i dansk strafferet - Kjær, Morten (Nordisk Tidsskrift for Kriminalvidenskab, 2017)
This article deals with the history of the principle of legality in Danish criminal law. The principle of legality is a relatively new invention and was first introduced with the criminal code of 1866 § 1. Before that, courts were given broad discretion in criminal cases. This discretion must be viewed as the logical consequence of the lack of a comprehensive and systematic criminal code such as that first issued in 1866 where it replaced the sixth book in the National Law of Denmark 1683. With the promulgation of a new systematic criminal code it was possible to introduce the principle of legality in Danish criminal law in 1866. While the principle of legality was designed to secure the predictability of the criminal law, measures were also taken in order to secure flexibility in the application of the code by the courts. The often casuistic definitions of the criminal offenses in the National Law of Denmark were thus replaced by abstract definitions and the courts were generally left with a wide margin of discretion when it came to questions of punishment. The criminal code of 1866 was thus built on a compromise between legality and flexibility.